Removal of 2, 4, 6 trichlrophenol from simulated wastewater via progressive freeze concentration: effect of initial concentration with the usage of response surface methodology as the means of optimization - Mazzam, Anwar Addini (2020)
2, 4, 6-Trichlorophenol (TCP) has been used primarily in various pesticide formulations and as a wood preservative. Only the slightest amount of TCP in wastewater is harmful and it can be the cause of many diseases, thus the importance to remove the TCP from wastewater is crucial. Progressive freeze concentration (PFC) process is a versatile process that can be used to separate solution from its contaminant. PFC is a method of separating solution and solvent into a singular layer of ice on the wall where coolant is applied. In this study, PFC was used to remove TCP from a simulated wastewater.